On the occurrence of Ipomoea imperati (Vahl) Griseb. (Convolvulaceae, Ipomoeeae) within coastal dunes of Tunisia, the lost piece of the puzzle fell into place! - El Mokni, Ridha (UMA Editorial, 2025)
The occurrence of Ipomoea imperati(Vahl) Griseb. is here confirmed and clearly documented for the first time in Tunisia following botanical surveys recently carried out on coastal dunes within the north-western and central-eastern part of the country. General characteristics as well as original photographs are here provided for the Tunisian material. Phenology, habitat and ecological notes of the species in Tunisia are presented. Moreover, a discriminating key for known species of the genus in Tunisia is proposed

La presencia de Ipomoea imperati (Vahl) Griseb. se confirma y documenta claramente por primera vez en Túnez tras estudios botánicos realizados recientemente en las dunas costeras del noroeste y centro-este del país. Se proporcionan características generales y fotografías originales del material tunecino. Se presentan la fenología, el hábitat y las notas ecológicas de la especie en Túnez. Además, se propone una clave de discriminación para las especies conocidas del género en Túnez.
Sobre la presencia de Ipomoea imperati(Vahl) Griseb. (Convolvulaceae, Ipomoeeae) en las dunas costeras de Túnez, ¡la pieza perdida del rompecabezas encajó!
Keywords: Plantas - Clasificación; Convolvuláceas; Fitogeografía; Corología; Convolvulus; Dunas costeras; Norte de África; Solanales